Complex executive functions assessed by the trail making test (TMT) part B improve more than those assessed by the TMT part A or digit span backward task during vagus nerve stimulation in patients with drug-resistant epilepsy - Lähde, Niina; Basnyat, Pabitra; Raitanen, Jani; Kämppi, Leena; Lehtimäki, Kai; Rosti-Otajärvi, Eija; Peltola, Jukka (Frontiers in Psychiatry, 2024)
Introduction: There is a paucity of clinical studies examining the long-term effects of vagus nerve stimulation (VNS) on cognition, although a recent study of patients with drug-resistant epilepsy (DRE) treated with VNS therapy demonstrated significant improvement in executive functions as measured by the EpiTrack composite score. The present study aimed to investigate performance variability in three cognitive tests assessing executive functions and working memory in a cohort of DRE patients receiving VNS therapy during a follow-up duration of up to five years. Methods: The study included 46 DRE patients who were assessed with the Trail Making Test (TMT) (Parts A and B) and Digit Span Backward (DB) task prior to VNS implantation, 6 months and 12 months after implantation, and yearly thereafter as a part of the clinical VNS protocol. A linear mixed-effects (LME) model was used to analyze changes in test z scores over time, accounting for variations in follow-up duration when predicting changes over five years.Additionally, we conducted descriptive analyses to illustrate individual changes.On average, TMT-A z scores improved by 0.024 units (95% confidence interval (CI): 0.006 to 0.042, p = 0.009), TMT-B z scores by 0.034 units (95% CI: 0.012 to 0.057, p = 0.003), and DB z scores by 0.019 units per month (95% CI: 0.011 to 0.028, p < 0.001). Patients with psychiatric comorbidities achieved the greatest improvements in TMT-B and DB z scores among all groups (0.0058 units/month, p = 0.036 and 0.028 units/month, p = 0.003, respectively). TMT-A z scores improved the most in patients taking 1-2 ASMs as well as in patients with psychiatric comorbidities (0.042 units/month, p = 0.002 and p = 0.003, respectively).Performance in all three tests improved at the group level during the follow-up period, with the most robust improvement observed in TMT-B, which requires inhibition control and set-switching in addition to the visuoperceptual processing speed that is crucial in TMT-A and working-memory performance that is essential in DB. Moreover, the improvement in TMT-B was further enhanced if the patient had psychiatric comorbidities.